2023
DOI: 10.3390/ijerph20065040
|View full text |Cite
|
Sign up to set email alerts
|

The Effect and Cost-Effectiveness of Offering a Combined Lifestyle Intervention for the Prevention of Cardiovascular Disease in Primary Care: Results of the Healthy Heart Stepped-Wedge Trial

Abstract: Objective: To evaluate the effectiveness and cost-effectiveness of offering the combined lifestyle programme “Healthy Heart”, addressing overweight, diet, physical activity, smoking and alcohol, to improve lifestyle behaviour and reduce cardiovascular risk. Design: A practice-based non-randomised stepped-wedge cluster trial with two-year follow-up. Outcomes were obtained via questionnaires and routine care data. A cost–utility analysis was performed. During the intervention period, “Healthy Heart” was offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Remarkably, the most prevalent mentioned barrier was that patients were not informed about the existence of the programme. This also puts the results of the effectiveness and cost-effectiveness study in a different light; 23 this study investigated whether implementing the HH programme was effective and cost-effective on a population level by giving lifestyle change a boost during the intervention period. Implementation of the programme in general practices was found not to be effective or cost-effective on a population level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, the most prevalent mentioned barrier was that patients were not informed about the existence of the programme. This also puts the results of the effectiveness and cost-effectiveness study in a different light; 23 this study investigated whether implementing the HH programme was effective and cost-effective on a population level by giving lifestyle change a boost during the intervention period. Implementation of the programme in general practices was found not to be effective or cost-effective on a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness, maintenance and cost-effectiveness are discussed in a separate paper. [23] Qualitative data: Experiences of health care providers (HCPs) and eligible patients Both GP practices and eligible patients were selected by purposive sampling. Both patients that participated (further referred to as participants) and patients that did not participate (further referred to as non-participants) in the HH-programme were recruited from the HH-study.…”
Section: Quantitative Data: Re-aimmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that awareness and knowledge among GPs regarding content and effectiveness of healthcare innovations, such as CLIs, are crucial for developing a positive attitude towards these innovations. 37,[42][43][44] Therefore, providing education and involvement of the GP could contribute to increased referrals to CLIs. A positive development is that healthcare insurances have started to reimburse CLIs in January 2019 in the Netherlands.…”
Section: Implications For Practicementioning
confidence: 99%